An in vitro screening technique for the identification of grain mould resistance in sorghum - S.S. NAVI, S.D. SINGH and (Indian Phytopathology, 2002)
Grain mould (GM) is the most important biotic constraint of sorghum [Sorghum bieolor (L.) Moench] in India and other parts of the world and host plant resistance is the most convenient method o( control of this disease. Breeding for disease resistance has been slow due to the total reliance on field screening which is used once-a-year during rainy season. In order to conduct screening independent of season and to detect possible escapes from field screening, an in vitro screening technique has been developed. The technique involves dip inoculation of mature seed in a mixed spore suspension (lx106 spores ml’) of major GM fungi (Fusarium moniliforme, F. pallidoroseum, and Curvularia lunata), transferring inoculated seed to the pre-sterilized petridish humid chamber @ 25 seed plate+, and their incubation at 28Â±1Â°C with or without light for 5 days. Visual evaluation of mould infection was done on 1-9 scale (1 = no colonization, and 9 = >75% seed surface colonization by the mould fungi) using an illuminated magnifier. The efficiency of the technique was measured by comparing mean grain mould scores (MGMS) of 43 accessions evaluated at Bhavanisagar, Mysore and Patancheru in India. There was a significant correlation (P<O.Ol) between ill vitro MGMS and field scores at or across three locations. Of the 66 photoperiod sensitive accessions that were screened using the in vitro screening, 14 showed high level of resistance even under field disease nursery situation. The usefulness of the technique in GM resistance program is discussed.